The Representation of Social Actors in EFL Textbooks: Systemic Functional Linguistics Perspective - Stanislaus Guna; Hieronimus Canggung Darong (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
Systemic Functional Linguistics (SFL) has gained popularity as a linguistic theory, especially in the field of education where it provides a useful method for examining textbooks. The goal of this study is to examine how social actors are portrayed in a particular textbook utilizing SFL framework. Textual data were gathered from a sample of the textbook, and transitivity patterns of process categories and pronoun usage were used to analyze the data. The results revealed that the pronoun